1996
DOI: 10.1093/oxfordjournals.humrep.a019423
|View full text |Cite
|
Sign up to set email alerts
|

Ovary and ovulation: Low temperature storage and grafting of human ovarian tissue

Abstract: Ovarian tissue storage at low temperatures is a promising new method for protecting young cancer patients from the sterilizing effects of chemotherapy and/or radiotherapy. Tissue can be stored and returned to the body in due course as a thin cortical graft since the primordial follicles are distributed peripherally and are relatively resistant to ischaemia. Slices of tissue donated by healthy patients were trimmed to a uniform size and preserved by slow freezing to liquid nitrogen temperatures for up to 2 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
252
3
14

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 504 publications
(282 citation statements)
references
References 0 publications
9
252
3
14
Order By: Relevance
“…Based on the literature [12] and [16], EG was more effective at protecting cells during cryopreservation than GLY, perhaps due to its low toxicity and efficient permeability [51]. Although some authors [12], [16] and [18] have shown that GLY is inferior to the other cryoprotectants, in our study the percentage of normal preantral follicles after cryopreservation in GLY was similar to EG. It is noteworthy that we used a different slow freezing curve and a removal procedure for GLY similar to the employed by Candy et al [12].…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Based on the literature [12] and [16], EG was more effective at protecting cells during cryopreservation than GLY, perhaps due to its low toxicity and efficient permeability [51]. Although some authors [12], [16] and [18] have shown that GLY is inferior to the other cryoprotectants, in our study the percentage of normal preantral follicles after cryopreservation in GLY was similar to EG. It is noteworthy that we used a different slow freezing curve and a removal procedure for GLY similar to the employed by Candy et al [12].…”
Section: Discussionsupporting
confidence: 63%
“…However, results obtained by Candy et al [12] using GLY (4.3-28.3 and 16.3-32%: survival of primordial and primary follicles, respectively) were comparable to those for caprine preantral follicles in our experimental conditions. Another report in human ovarian tissue [18] using a freezing protocol similar to Candy et al [12], i.e. slow freezing curve and fast removal of GLY without sucrose, obtained only 10% viable preantral follicles after freezing and thawing.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations